In situ formation of a 3D core-shell and triple-conducting oxygen reduction reaction electrode for proton-conducting SOFCs - Zhang, Zhenbao (2019)
BaZrxCeyY1-x-yO3-δ are recognized proton-conducting electrolyte materials for proton-conducting solid oxide fuel cells (H+-SOFCs) below 650 °C. Here Co cations are incorporated into the BaZr0.4Ce0.4Y0.2O3-δ (BZCY) scaffold to generate a 3D core-shell and triple-conducting (H+/O2−/e−) electrode in situ via infiltrating and reactive sintering. The core is the bulk BZCY scaffold, while the shell is composed of the cubic Ba(Zr0.4Ce0.4Y0.2)1-xCoxO3-δ, cubic spinel Co3O4 and cubic fluorite (Ce, Zr, Y)O2. The obtained electrode exhibits an excellent compatibility with the BZCY electrolyte, and performs well in yielding a low and stable polarization resistance for oxygen reduction reaction for intermediate-temperature H+-SOFCs. In particular, it achieves polarization resistances as low as 0.094 and 0.198 Ω cm2 at 650 and 600 °C in wet air (3% H2O) when the sintering temperature for the electrode is 900 °C. In addition, a symmetrical cell also exhibits operation stability of 70 h at 650 °C. Furthermore, a fuel cell assembled with the 3D core-shell and triple-conducting electrode delivers a peak power density of ∼330 mW cm−2 at 650 °C. The substantially improved electrochemical performance and high stability are ascribed to the unique core-shell structure and the formation of Ba(Zr0.4Ce0.4Y0.2)1-xCoxO3-δ in the shell.